Etika Mengkritik Pemerintah Dalam Tafsir Bahasa Jawa (Studi Pragmatik Terhadap Tafsir Al-Ibriz Karya KH. Bisri Mustofa) - Shella Nur Azizah; Ahmad Faruk (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2024)
This thesis is motivated by the facts about the ethics of criticism contained in Tafsir Al-Ibriz Li Ma'rifat Al-Tafsir Al-Qur'an Al-'Aziz. It is a Javanese commentary book written using pegon letters. This book of interpretations was compiled by KH. Bisri Must}ofa. Meanwhile, in pragmatic theory it is said that messages in criticism can be understood through the ethics of the person criticizing. Therefore, this thesis formulates the problem with the aim of finding out: (1) The ethics of criticizing in the interpretation of Al-Ibriz by KH. Bisri Must}ofa. (2) Application of pragmatic parameters 'ethics of criticism' in the interpretation of Al-Ibriz by KH. Bisri Must}ofa. The method used in this research is qualitative with descriptive data analysis techniques. This research uses literature review, where the data used comes from the Al-Qur'an, books and previous research. After obtaining relevant references, the author then compiles and analyzes the data using pragmatic theory. The results of the research show that the ethics of criticizing in the interpretation of Al-Ibriz use a pragmatic approach, namely, (1) criticism is conveyed in polite and smooth language, so that criticism can be well received. (2) criticism is delivered with full respect and politeness, so that a harmonious relationship can be created between the person criticizing and the person being criticized.